Grounded futures: A decade of planning through humanitarian and Southern lenses - Batoul Ibrahim (PlaNext)
This reflective article marks the tenth anniversary of plaNext – Next Generation Planning, tracing its evolution as a critical platform for spatial planning discourse, particularly in humanitarian and Global South contexts. Drawing on personal editorial and field-based experience, the author explores how plaNext has shifted spatial planning discourse toward inclusion, ethics, and contextual sensitivity. Focusing on contributions from Volumes 9 to 11, the article highlights planning’s potential as a transformative tool in humanitarian settings, centering community agency, participatory methods, and interdisciplinary innovation. The analysis further integrates non-Western ethical frameworks, advocating for planning as a reparative and care-based practice, especially relevant in post-crisis urban environments. Contributions from the Global South illustrate planning as a reparative practice rooted in justice, resilience, and relational well-being. Ultimately, the article calls for bridging academic and humanitarian spheres to foster responsive, interdisciplinary, and just planning. The next decade of plaNext offers a chance to consolidate many gains and push further. Thus, the journal’s commitment to fostering a young researchers-driven process is vital for the future of spatial planning.